Metabolomic and transcriptomic analysis reveals the molecular mechanism by which blue light promotes lutein synthesis in strawberry - Xiao-dong CHEN; Wei-jian CAI; Jin XIA; Hua-zhao YUAN; Qing-lian WANG; Fu-hua PANG; Mi-zhen ZHAO (Journal of Integrative Agriculture)
Carotenoids are an important component of the human diet, and fruit is a primary source of carotenoids. The synthesis and regulation of carotenoids in fruit are important contributors to the formation of fruit quality. In China, strawberry is one of the main seasonal fruits grown in the winter. Previous studies have shown that light has a significant effect on the metabolism of anthocyanins, sugars, and polyphenols in strawberry. However, the understanding of the role of light in regulating the metabolism of carotenoids in strawberry remains limited. This study investigated the effects of blue, red, yellow-green, and white light on carotenoid metabolism in strawberry. Blue light treatment promoted the synthesis of multiple carotenoids, including lutein, compared with the other three treatment groups. The RNA sequencing data revealed that blue light treatment promoted the expression of lycopene ε-cyclase (LCYE), and the transient overexpression of LCYE in strawberry fruit promoted lutein accumulation in strawberry. Overall, the results suggest that blue light can promote the synthesis of lutein in strawberry by inducing the expression of LCYE.